Am I a STEM professional? Documenting STEM student professional identity development. Issue 4 (3rd April 2017) - Nadelson, Louis S.; McGuire, Sharon Paterson; Davis, Kirsten A.; Farid, Arvin; Hardy, Kimberly K.; Hsu, Yu-Chang; Kaiser, Uwe; Nagarajan, Rajesh; Wang, Sasha
Abstract : Post-secondary education is expected to substantially contribute to the cognitive growth and professional achievement of students studying science, technology, engineering, and mathematics (STEM). Yet, there is limited understanding of how students studying STEM develop a professional identity. We used the lens of self-authorship to develop a model for STEM student professional identity development. We applied the model to frame our assessment of the relationship between the level of STEM students' perceptions of their professional identities and their educational experiences, learning preferences, and comfort with faculty interactions. We found a misalignment between students' perception of themselves as professionals and the expectations for their actions in professional situations. We also found that students engaged in learning activities similar to the activities of STEM professionals communicated higher levels of professional identity development. We provide implications for our research and directions for ongoing investigations.